Ideology, emancipation and prophetic religion - Caviglia, Alessandro (2017)
The present work arises from the philosophy of religion and presents the way in which certain forms of religion introduce themselves as a form of ideology whose purpose is to connect people with the ideals of neoliberalism. It is in this sense that a study of the so-called Theology or Gospel of Prosperity is carried out. As an antidote to this form of ideology, it proposed to strengthen the prophetic voice of religion.